2021
DOI: 10.1007/s00429-021-02290-z
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the basal forebrain to corticocortical network interactions

Abstract: Basal forebrain (BF) cholinergic neurons provide the cerebral cortex with acetylcholine. Despite the long-established involvement of these cells in sensory processing, attention, and memory, the mechanisms by which cholinergic signaling regulates cognitive processes remain elusive. In this study, we recorded spiking and local field potential data simultaneously from several locations in the BF, and sites in the orbitofrontal and visual cortex in transgenic ChAT-Cre rats performing a visual discrimination task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…The cholinergic system has long been known to strongly influence cortical plasticity. 3 , 43 , 44 , 45 , 46 , 47 A line of studies has demonstrated that pairing auditory stimuli with cholinergic stimulation reorganizes cortical sensory representations, known by the term “receptive field plasticity.” 23 , 24 Furthermore, recent studies showed that cholinergic inputs may even endow primary sensory cortices with non-sensory representations not expected previously. 48 , 49 In particular, Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The cholinergic system has long been known to strongly influence cortical plasticity. 3 , 43 , 44 , 45 , 46 , 47 A line of studies has demonstrated that pairing auditory stimuli with cholinergic stimulation reorganizes cortical sensory representations, known by the term “receptive field plasticity.” 23 , 24 Furthermore, recent studies showed that cholinergic inputs may even endow primary sensory cortices with non-sensory representations not expected previously. 48 , 49 In particular, Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…2 , have focused on the BF as playing a central role in modulation of DMN activity across a number of experimental modalities. The BF has been shown to be a major neuromodulatory hub, supporting broad functional connections with neocortical and subcortical brain regions critical to cognition ( Lin et al, 2015 ; Yang et al, 2017 ; Zaborszky et al, 2018 ; Gombkoto et al, 2021 ). Further, degeneration of BF across age and with certain neuropathological conditions, such as Alzheimer’s disease, has been associated with both functional and cognitive impairment ( Schmitz et al, 2016 ; Markello et al, 2018 ).…”
Section: Subcortical Control Of the Dmn: Role Of The Basal Forebrainmentioning
confidence: 95%
“…These cell groups can modulate the activity of neurons located in the prefrontal cortices, hippocampi, and amygdala primarily by activating cholinergic receptors ( 16 ). These projections are organized in clusters, based on both topographical and functional principles, which allow for a spatially selective modulation of individual or joint cortical areas ( 25 27 ). Briefly, more medial-anterior located neurons of the BFCN project to the medial frontal cortex, while the substantia innominata, the nucleus basalis of Meynert, and the diagonal band neurons project to dorsal regions of prefrontal cortical areas.…”
Section: Neuroanatomical Organization Of the Bfcnmentioning
confidence: 99%
“…Beyond the structural integrity, evidence suggests that ACh levels are linked with distinct cognitive functions. For instance, it has been shown that transient rises in prefrontal ACh are associated with increased visual cue detection, indicating a link between ACh levels and attention ( 25 ). In support, ACh increases, measured via microdialysis, were related to increased task performance ( 31 ).…”
Section: Role Of the Cholinergic System In Cognitionmentioning
confidence: 99%